The art of papercraft - Hiebert, Helen, 1965- (Storey Publishing, 2022)
"Paper artist and teacher Helen Hiebert compiles a one-of-kind collection of 40 unique projects, each using just one sheet of paper, combining decorative paper techniques like marbling, stamping, and stenciling with dimensional techniques like origami, cutting, folding, quilling, stretching, weaving, and pop-ups"--